SÍNTESE DE NAFTOQUINONAS HETEROCÍCLICAS SELENOFUNCIONALIZADAS DE INTERESSE FARMACÊUTICO - Aline Alves dos Santos Naujorks (2021)
Selenium-containing naphthoquinones are biologically relevant hybrid structure and can be used for diverse biological activities. In this thesis we planned to synthesize a series of new selenium-functionalized naphthoquinone derivatives, from the reaction of (E)-2-(dec-1-en-3-yl)-3-hydroxynaphthalene-1,4-dione and structurally diverse diorganoyl diselenides, by utilizing I2/DMSO catalytic oxidant system. By using our methodology, six new selenylated products were obtained and their structures were confirmed by using spectroscopic and spectrometric techniques. Structural factors influenced the electrophilic properties of quinonoid molecules, forming mainly o-quinones compounds, such as the compound 2-heptyl-3-(phenylselanyl)-3,4-dihydro-2H-benzo [h] chromene-5,6-dione. Starting from p-methoxy diphenyl diselenide, o- and p-naphthoquinone derivatives were obtained. In general, the reactions resulted in the selenylated products in low yields. However, due to the interesting feature of this hybrid structure, we extended our studies to other substituted diselenides, and it was possible to obtain a series of new compounds with biological and pharmaceutical interest.